Post-processing of thermal infrared images and analysis on TRAM blood perfusion mapping in breast tissue reconstruction - Muhammad Syarifuddin Mohamed Hamli (2019)
In breast reconstruction surgery, the operation itself is a delicate process and the risk of the reconstructed flap developing flap necrosis is always high. Several studies had demonstrated that the usage of active dynamic thermography in the preoperative planning of breast reconstruction showed a promising outcome in preventing such complications. However, there was a lack of research in thermographic examinations of the flap intraoperatively and postoperatively. This project aimed to determine the efficacy of using a single image reconstruction method in detecting complications by analysing the active dynamic thermography of Transverse Rectus Abdominis Musculocutaneous (TRAM) flap pre-, intra and postoperatively. In this present study, over 260 sample sizes of series of transient thermal infrared images captured were reconstructed and enhanced to a single image using the Tissue Activity Ratio (TAR) approach. Based on the surgical results, the single reconstructed image obtained was statistically analysed to compare between patients with complications and without complication. Initial findings had discovered that the single image obtained was of high contrast and hence, the thermal activity and blood perfusion of the flap could be evaluated. Furthermore, there was a significant difference in the TAR image produced between patients who developed non-necrotic flaps and necrotic flaps. Results obtained using this devised TAR method had shown to be an excellent assessment tool and diagnostic method in the application of active dynamic thermography in the biomedical field.